Gender Innovation and Migration in Switzerland - Falk, Francesca; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
(3z(BThis highly informative book provides precisely analysed situations highlighting migration$1 (Bs crucial role for emancipatory change and hence socio-political innovation. A so far hidden perspective is being made visible and contributes a highly compelling piece for rewriting Switzerland$1 (Bs history.(3y $1 (BJulia Nentwich, Research Institute for Organisational Psychology, University of St. Gallen, Switzerland (3z(BFrancesca Falk proposes a migrantisation of the history of gender equality in Switzerland. It was women with experience of migration who were engaged on behalf of women's suffrage with special verve. It was working Italian women in particular who created the conditions for the expansion of childcare infrastructure.(3y $1 (BElisabeth Joris, Historian, Zurich, Switzerland (3z(BInstead of sidelining issues of migration and gender, as is done so often, this important book teaches us that these perspectives must be central to any substantial narration of Swiss history.(3y $1 (BPatricia Purtschert, Interdisciplinary Centre for Gender Studies, University of Bern, Switzerland This open access book analyses migration and its relation to socio-political transformation in Switzerland. It addresses how migration has made new forms of life possible and shows how this process generated gender innovation in different fields: the changing division of work, the establishment of a nursery infrastructure, access to higher education for women, and the struggle for female suffrage. Seeing society through the lens of migration alters the perspective from which our past and thus our present is told$1 (Band our future imagined. Francesca Falk is Senior Lecturer in Contemporary History at the University of Fribourg, Switzerland.s
1. Introduction -- 2. Conceptual Clarifications -- 3. Changing Gendered Divisions of Work -- 4. Nurseries -- 5. Higher Education -- 6. Female Suffrage -- 7. Conclusion: An Awareness of Alternatives.
Keywords: Europe -- Politics and government; Emigration and immigration; Comparative government; European Politics; Human Migration; Comparative Politics